Clinical utility of cerebrospinal fluid Alzheimer’s disease biomarkers in the diagnostic workup of complex patients with cognitive impairment - Ming-Yu Wang; Ke-Liang Chen; Yu-Yuan Huang; Shu-Fen Chen; Rong-Ze Wang; Yi Zhang; He-Ying Hu; Ling-Zhi Ma; Wei-Shi Liu; Jun Wang; Jia-Wei Xin; Xue Zhang; et al. (Translational Psychiatry)
Abstract Cerebrospinal fluid (CSF) biomarkers have been widely adopted in Alzheimer’s disease (AD) diagnosis. However, no studies focused on the application of CSF biomarkers in the clinical practice of complex and atypical patients with cognitive impairment in China. This study aimed to evaluate the added value of CSF AD biomarkers in cognitively impaired patients with complex conditions in a memory clinical setting. A total of 633 participants were included from the National Center for Neurological Disorders in Shanghai, China. The CSF AD biomarkers were measured with ELISA. Cutoff values were firstly identified using Youden’s index. The neurologists proposed etiology diagnosis with a percentage estimate of their confidence and prescribed medication before and after CSF disclosure. Changes in etiological diagnosis, diagnostic confidence, and management plan were compared across the groups. Of the 633 patients (mean [SD] age, 61.1 [11.3] years; 295 males [46.6%]), 372 (58.8%) were diagnosed with dementia, 103 (16.3%) with mild cognitive impairment, and 158 (24.9%) with subjective cognitive decline. Using those pre-defined cutoffs, we categorized patients into 3 groups: Alzheimer’s continuum (68.1%), non-AD pathologic change (11.1%), and normal AD biomarkers (20.8%). After CSF disclosure, the proposed etiology changed in 158 (25.0%) participants and the prescribed medication changed in 200 (31.6%) patients. Mean diagnostic confidence increased from 69.5–83.0% (+13.5%; P < 0.001). In conclusion, CSF AD biomarkers significantly impacted the diagnosis, diagnostic confidence, and treatment plans for Chinese patients with complex cognitive impairment. CSF AD biomarkers are a useful tool for clinicians beyond routine clinical assessment.